Advertising of medical devices on the Internet - Vargas Portillo, Patricia (Opción, 2020)
Nowadays, Internet is increasingly being used to acquire pharmaceuticals, foodsupplements and medical devices. Although there is a set of rules established in thisregard, they are not sufficient. For this reason, the industry has established a list ofethical standards that complement them, benefiting all sectors that interact in this area